Study on CNT reinforced functionally graded sandwich conical shell subjected to low-velocity impact under thermal environment. (April 2022) - Das, Apurba
In the present work, low-velocity impact behavior of pre-twisted carbon nanotubes (CNTs) reinforced functionally graded (FG) sandwich conical shell panels is studied using finite element method. The top and bottom face sheets are reinforced with single-walled CNTs reinforced FG materials with various patterns. The temperature-dependent material properties of the CNTs reinforced functionally graded facings are evaluated using micromechanical models. The dynamic equilibrium equation of the impacted sandwich panel is formulated using Lagrange's equation. A modified Hertzian contact law is used to evaluate contact force. The solutions of the resulting equations are obtained using Newmark's time integration method. After validation study of the present method, the effects of the CNTs grading pattern, velocity of the impactor, size of the impactor, CNTs volume fraction, operating temperature, angle of twist, and core-to-facing thickness ratio on the low-velocity impact response of the CNTs reinforced functionally graded sandwich conical shell panel are studied in detail. Numerical results show that increasing the volume fraction of CNTs increases the contact force while a lower contact force is predicted at elevated temperatures.